Regulation of Metabolism by Mitochondrial MUL1 E3 Ubiquitin Ligase - Cilenti, Lucia; Mahar, Rohit; Di Gregorio, Jacopo; Ambivero, Camilla T.; Merritt, Matthew E.; Zervos, Antonis S. (Frontiers in Cell and Developmental Biology, 2022)
MUL1 is a multifunctional E3 ubiquitin ligase that is involved in various pathophysiological processes including apoptosis, mitophagy, mitochondrial dynamics, and innate immune response. We uncovered a new function for MUL1 in the regulation of mitochondrial metabolism. We characterized the metabolic phenotype of MUL1(-/-) cells using metabolomic, lipidomic, gene expression profiling, metabolic flux, and mitochondrial respiration analyses. In addition, the mechanism by which MUL1 regulates metabolism was investigated, and the transcription factor HIF-1α, as well as the serine/threonine kinase Akt2 were identified as the mediators of the MUL1 function. MUL1 ligase, through K48-specific polyubiquitination, regulates both Akt2 and HIF-1α protein levels and the absence of MUL1 leads to the accumulation and activation of both substrates. We used specific chemical inhibitors, and activators of HIF-1α and Akt2 proteins, as well as Akt2(-/-) cells, to investigate the individual contribution of HIF-1α and Akt2 proteins to the MUL1-specific phenotype. This study describes a new function of MUL1 in the regulation of mitochondrial metabolism and reveals how its downregulation/inactivation can affect mitochondrial respiration and cause a shift to a new metabolic and lipidomic state.